2006
DOI: 10.1007/s10517-006-0429-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic consumption of sodium valproate and melatonin on seizure activity in Krushinskii-Molodkina rats

Abstract: Experiments on Krushinskii-Molodkina rats with hereditary predisposition to audiogenic seizures showed that chronic consumption of aqueous solution of melatonin (50 mg/liter) had no effect on the pattern of seizures induced by 20-fold acoustic stimulation. Sodium valproate (50 mg/liter) insignificantly decreased the seizure response. Combined treatment with sodium valproate and melatonin produced a potent anticonvulsant effect, i.e. increased the latency and decreased the severity of audiogenic seizures. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The potential benefits of melatonin have been evaluated in patients with and in animal models for Alzheimer’s disease (Srinivasan et al, 2006), amyotrophic lateral sclerosis (ALS) (Weishaupt et al, 2006), Parkinson’s disease (Willis and Armstrong, 1999; Medeiros et al, 2007), stroke (Kilic et al, 2004; Dominguez-Rodriguez et al, 2007), epilepsy (Gupta et al, 2004; Savina et al, 2006), and traumatic brain injury (Ozdemir et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of melatonin have been evaluated in patients with and in animal models for Alzheimer’s disease (Srinivasan et al, 2006), amyotrophic lateral sclerosis (ALS) (Weishaupt et al, 2006), Parkinson’s disease (Willis and Armstrong, 1999; Medeiros et al, 2007), stroke (Kilic et al, 2004; Dominguez-Rodriguez et al, 2007), epilepsy (Gupta et al, 2004; Savina et al, 2006), and traumatic brain injury (Ozdemir et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…73 Moreover, melatonin increases brain g-aminobutyric acid concentrations and receptor affinity 74 and potentiates brain inhibitory transmission via g-aminobutyric acid synapses. 75 In animal models, melatonin can inhibit audiogenic 76 and electrical seizures 77 as well as reduce convulsions induced by pentetrazole, 78 pilocarpine, 79 L-cysteine, 80 and kainate. 81 Peled et al showed improvement in seizure activity in five of six children with intractable seizures when melatonin was combined with an antiepileptic drug.…”
Section: Childhood Seizure Disordersmentioning
confidence: 99%
“…Melatonin and valproic acid. Prolonged melatonin administration in rats congenitally predisposed to audiogenic convulsions (the Krushinsky-Molodkina model) had no effect on seizures evoked by a 20 times more powerful auditory stimulus (Savina et al, 2006). VPA administration significantly reduced convulsions but VPA and melatonin combination had a significantly larger anti-seizure effect: it lengthened latency time and reduced seizure severity.…”
Section: The Audiogenic Seizure Modelmentioning
confidence: 99%